ANALISIS DETERMINAN MAKRO EKONOMI DAN SOSIAL TERHADAP TABUNGAN DOMESTIK DI KALIMANTAN TENGAH PERIODE 2010-2023 - Jannah, Miftakhul; Fauzi, Risky Ahmad; Sagala, Desi Triana; Kristiani, Yonita; Sitanggang, Kanna Enjelina; Pardede, Wenty Magdalena; Donovan, Arian; Purba, Christian Posmadi; Hukom, Alexandra (STIE Jambatan Bulan, 2025)
This study analyzes the influence of macroeconomic and social determinants on domestic savings in Central Kalimantan during 2010-2023. Using the Engle-Granger Error Correction Model (EG-ECM) with time series data from the Central Statistics Agency, Bank Indonesia, and Ministry of Finance, this research examines the relationship between Gross Regional Domestic Product (GRDP), Dependency Ratio, Open Unemployment Rate, and Human Development Index as independent variables against Domestic Savings as the dependent variable. The findings reveal significant differences between short-term and long-term dynamics. In the long run, GRDP shows a positive and significant effect with an elasticity of 0.862, while the Human Development Index demonstrates a consistently negative and significant impact in both time horizons with coefficients of -2.719 (short- term) and -2.042 (long-term), indicating a trade-off between human capital investment and financial savings accumulation. Dependency Ratio and Open Unemployment Rate show no significant effects in either period, challenging conventional theories applied in developed countries. The Error Correction Term coefficient of -1.672 indicates overshooting in the adjustment process toward long-term equilibrium.